Applications of teledentistry in dental practice: a systematic review - Fortich-Mesa, Natalia; Hoyos-Hoyos, Vivi (Revista Facultad de Odontología Universidad de Antioquia, 2020)
Introduction: access to dental services in rural and remote areas is a problem still to be solved; for this purpose, a new alternative known as teledentistry has emerged. Through the application of information and communications technologies (ICTs), teledentistry promotes prevention, diagnosis, and treatment. This study aimed to determine the impact of teledentistry applications on clinical practice in different specialties based on the current evidence in the literature. Methods: two reviewers conducted a literature search in PubMed, EMBASE, EBSCO, ScienceDirect and LILACS databases until August 2019, to identify studies published in English, Spanish and Portuguese. Studies containing interventions applied to teledentistry, published in the last six years and available in full text were included. Bias risk was assessed through validated criteria according to each study type. Results: the search strategy retrieved 1028 articles, 24 of which were selected for evaluation. Twenty-three articles were cross-sectional studies and only one study was quasi-experimental. Seventeen studies (70.8%) considered teledentistry as an alternative to diagnosing and treating oral diseases in rural areas and health centers through mobile devices and clinical photographs. Most studies had moderate to high bias risk. Conclusion: while there is evidence on the use of teledentistry in the various fields of dentistry, it is important to keep in mind that since this is a novel tool that seeks to support access to health services in remote areas, the obtained results are preliminary, and further research with quality publications is necessary to evaluate the effectiveness of this tool